'You cannot expect miracles to happen overnight': patience pays off when you wish to establish a new adrenocortical carcinoma cell line. Issue 2 (1st July 2021) - Lalli, Enzo
Abstract : Growing attention is being paid to the association of adrenocortical carcinoma (ACC), a rare endocrine malignancy, to cancer predisposition syndromes caused by germline mutations in genes involved in the control of genome stability. Tumour cells with a defective DNA mismatch repair pathway have a high mutation burden, which results in the production of tumour-associated specific neoantigens and in an increase of the sensitivity to therapies that loosen the constraints of tumour attack by the immune system. The study by Landwehr et al. published in a recent issue of the European Journal of Endocrinology describes a patient with an aggressive ACC bearing a germline MUTYH mutation with loss of heterozygosity in the tumour and accumulation of 8-hydroxyguanine in its genomic DNA. The authors managed to establish a novel differentiated cell line from that tumour which bears the stigma of the defective DNA repair mechanism in its genome. The availability of this new cell model inside the expanding toolbox of the ACC cell lines will allow for novel experimental possibilities, in particular for the study of the tumour microenvironment and the response to immunotherapy.